Faktor-Faktor Kebijakan Yang Mempengaruhi Tabungan Mudharabah Pada Perbankan Syariah Di Indonesia - Sri Rahmany (LPPM ISNJ Bengkalis, 2020)
The first Islamic bank as a pioneer did not use an interesting system but instead used a profit-sharing system, namely Bank Muamalat Indonesia. The National Sharia Council has issued a fatwa stating that justified savings are savings based on Islamic principles, namely mudharabah and wadiah. The purpose of this research is to determine the effect of policy factors on mudharabah savings transactions in Islamic banking partially and simultaneously. This research uses a quantitative method where the data is in the form of a ratio. The population in this research 34 Islamic banks in Indonesia and were used as samples. The results of the research are statistically proven partially and simultaneously inflation, exchange rates and the BI Rate have a significant effect on mudharabah savings.